Caracterização acústica de cafés-concerto - António P. O. Carvalho (2008)
The goal of this work is to equip the project-architect with a tool easy to use, which supports him with helpful elements in the early stages of the conceptual phase of projecting Music-Clubs (rooms with a full capacity under 250 people, with live music or acting shows, with the possibility of consuming drinks or even light meals). Based on the eleven music-clubs studied in this work, it was possible to predict that the normalized reverberation time (RT) of these rooms (that is considering half of the room capacity) goes about 0.7 to 0.8 s for 500 to 2k Hz frequency bands. Considering that the predicted RT Maximum (difference between the RT with a full capacity room and the empty room RT), reaches average values of 0.4 s for the same frequencies, it is possible to predict that the normalized RT is about 0.7 or 0.8 ± 0.2 s, depending on the room being full or empty.